Analysis of Symmetry of Weight-Bearing in Athletes With and Without Low Back Pain during Gait - Meissam Sadeghisani; Vahid Sobhani; Hadi Azimi; Mohammad Taghi Karimi (The Society of Aging and Physical Activity (SAPA), 2018)
Background. Low Back Pain (LBP) is a prevalent phenomenon in athletes and asymmetrical loading on the limbs has been proposed as a risk factor related to this disease. Objectives. The purpose of the present study was to compare the asymmetry of loading applied on the legs between men with and without LBP during gait. Methods. A total of 40 participants, comprising 20 men with non-specific LBP who practiced martial arts and 20 men without LBP, participated in the study. The participants walked in gait lab and forces applied on the legs were recorded in three dimensions using a force plate. Also, asymmetry of the forces applied on the dominant and non-dominant limbs was measured. Results. The Asymmetry Indexes (ASI) of the first, second, and third peaks of vertical forces were respectively 3.1%, 3.4%, and 4.1% for normal participants and 4.2%, 4.2, and 2.1 for the participants who had LBP (p>0.05). Conclusion. It can be concluded that martial arts athletes with LBP apply symmetrical loads on the lower extremities, similar to healthy people.